Genotype and Phenotype Detection of E. coli Isolated from Children Suffering from Urinary Tract Infection - Zahraa Hameed Oda Alquraishi (Journal of Global Pharma Technology, 2018)
One hundred clinical urine samples were obtained from patients suffering from UTI during the period from 1, August, 2017 to 9, October, 2017. Methodology: The identification of the E. coli isolates was depended on colonial morphology, microscopic examination and biochemical tests as a primary identification. The final identification was performed by PCR technique with Mdh. In addition antibiotic genes were used such as (bla-CTM, blatem-1, aac (6) - Ib-crandsul-1). Result: Rendering  to  the  results  obtained  according to the morphological ,cultural and biochemical characters from 100 sample  only   80 (80%) isolate was  identify as  E. coli. According  to  the  results  obtained  by  PCR, Mdh gene  that  encode  was found in 56 (70%) isolates in  E. coli. The results of PCR revealed that the percentage of bla-CTX-M gene among tested isolates reached to 30/56(53.57%), 10/56(17.85%)   for blaTEM-1, 13/56(23.2%) for aac (6’)-Ib –cr and 33/42 (78.57%) for Sul-1gene. Conclusion: The  study  investigated  the  antibiotic resistance genes  of  E. coli which  play a major  role  in pathogen city .Keywords: E. coli, Urinary tract infection and antibiotic resistance genes.